2018
DOI: 10.3390/molecules23051125
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Catechins to Staphylococcal Enterotoxin A

Abstract: Staphylococcal enterotoxin A (SEA) is a toxin protein, and is the most common cause of staphylococcal food poisoning. Polyphenols, such as catechins, are known to interact with proteins. In this study, we investigated the binding of catechins to SEA using SPR (Biacore), Fourier transform infrared spectroscopy (FT-IR), isothermal titration calorimetry (ITC), and protein-ligand docking. We found that (−)-epigallocatechin gallate (EGCG) could strongly bind to SEA. According to thermodynamic parameters, a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…Therefore, whether the binding between EGCG and SEA was the essential factor for inhibiting the cytotoxicity of SEA was examined. Previous studies have shown that EGCG and (−)-4-Me-EGCG interact with SEA, and (−)-3 -Me-EGCG does not interact with SEA [18]. The only difference between EGCG and (−)-3 -Me-EGCG is the presence of a methyl group at the 3 -position of the galloyl group (Figure 4a).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Therefore, whether the binding between EGCG and SEA was the essential factor for inhibiting the cytotoxicity of SEA was examined. Previous studies have shown that EGCG and (−)-4-Me-EGCG interact with SEA, and (−)-3 -Me-EGCG does not interact with SEA [18]. The only difference between EGCG and (−)-3 -Me-EGCG is the presence of a methyl group at the 3 -position of the galloyl group (Figure 4a).…”
Section: Discussionmentioning
confidence: 83%
“…The strength of interaction between human serum albumin (HSA) having high homology to BSA and EGCG or a methylated EGCG was in the order of (−)-3 -Me-EGCG > (−)-4 -Me-EGCG > EGCG [26]. In previous studies, the strength of interaction between SEA and EGCG or a methylated EGCG was in the order of EGCG ≥ (−)-4 -Me-EGCG > (−)-3 -Me-EGCG [18]. The flavan-3-ol and the galloyl group of EGCG are essential for site-specific, high-affinity binding for serum albumin [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations